Genetic Diversity in Hexaploid and Tetraploid Wheat Genotypes Using Microsatellite Markers - Uddin, M.S.; Boerner, A. (Plant Tissue Culture and Biotechnology, 2009)
The genetic diversity of a set of hexaploid and tetraploid wheat germplasm at the IPK gene bank, Gatersleben, Germany was investigated by applying 13 wheat microsatellites (WMS). The materials consisted of 63 accessions of Triticum aestivum, T. dicoccon and T. durum obtained from different collection missions. In total, 126 alleles were detected with an average of 9.7 alleles per locus. The average PIC values per locus varied from 0.65 for the marker Xgwm192 to 0.88 for the marker Xgwm619. All the primer pairs revealed genetic heterogeneity in more than one genotype. Genetic dissimilarity values between genotypes, calculated by the WMS derived data, were used to produce a dendrogram. In the dendrogram the genotypes were clustered in nine clear groups. Key words: Genetic diversity, Microsatellite markers, Hexaploid, Tetraploid, Wheat genotype D.O.I. 10.3329/ptcb.v18i1.3267 Plant Tissue Cult. & Biotech. 18(1): 65-73, 2008 (June)